KESALAHAN EJAAN PADA PROPOSAL SKRIPSI MAHASISWA BIPA UIN RADEN MAS SAID SURAKARTA - Maharani, Siska Ayu; Khoiriyah, Salafia (Hasta Wiyata, 2021)
AbstractOne of the reasons for graduating students to become a bachelor of education must go through the scientific paper article stage. Thesis is one of the final assignments of academics, especially students as a form of accountability and implementation in a field which is held independently. This article was created to analyze spelling errors in the thesis proposals of BIPA students where there are still many errors in sentences, especially the spelling that is not in accordance with PUEBI. This research is interesting to study because it can see changes in the forms of language errors made by BIPA IAIN Surakarta students. Considering that in written or spoken language there is still a discrepancy with the rules of their second language, namely Indonesian. This is motivated by their first language which is still inherent in BIPA IAIN Surakarta learners. This study uses a qualitative descriptive approach to the process of solving problems and resolving them based on existing information objectively. Through detailed information sources, by looking for spelling errors and describing the error data found in several samples of BIPA IAIN Surakarta students. Analysis of the research data, the authors provide an overview under study in the form of a description. After researching the student's proposal, the results of the study showed that there were 68 language errors. 24% use of letters, 22% use of words, 32% use of punctuation, and 22% use typography. One thing that often happens is the use of punctuation marks.